Do reward systems influence performance in Ghana? Perspectives from staff of local government service - Adjei, Wisdom Sefiamor; Segbenya, Moses (Journal of Business and Enterprise Development (JOBED), 2024)
The study examined the effect of reward systems on employing performance among local government workers in Ghana. A quantitative approach with a descriptive survey design was adopted for the study. A sample of 172 respondents was drawn from a study population of 320 employees from Ho, Kpando and North Dayi districts in Ghana. Data was collected using a self-administered questionnaire, and responses were analysed with descriptive and inferential statistics. The study found that extrinsic factors—bonuses and housing loan schemes—significantly influenced performance among local government workers in Ghana. The reward systems were confronted with challenges such as lack of commitment from management, lack of funds to reward workers adequately, and lack of performance-based rewards systems. It was recommended that Municipal and District Chief Executives should use the housing loan scheme and bonuses to enhance performance among local government workers and institute a comprehensive performance-based rewards system for the local government workers in Ghana.